Si ( x ) = − ∫ x ∞ t sin ( t ) d t Ci ( x ) = − ∫ x ∞ t cos ( t ) d t
The functions Si ( x ) and Ci ( x ) are usually defined as above. Given that
∣ ∣ ∣ ∣ ∣ ∫ 0 ∞ sin ( x ) Si ( x ) d x + ∫ 0 ∞ cos ( x ) Ci ( x ) d x ∣ ∣ ∣ ∣ ∣ = C A π B ,
where A , B , C are all positive integers with A , C coprime. Find A + B + C .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Redefining the zone of integration:
− ∫ 0 ∞ ∫ x ∞ sin ( x ) t sin ( t ) d t d x = − ∫ 0 ∞ ∫ 0 t sin ( x ) t sin ( t ) d x d t = ∫ 0 ∞ t cos ( t ) sin ( t ) − t sin ( t ) d t
Falling a similar procedure: ∫ 0 ∞ cos ( x ) Ci ( x ) d x = − ∫ 0 ∞ t sin ( t ) cos ( t ) d t
Now using the Dirichlet integral ∫ 0 ∞ x sin ( x ) d x = 2 π The answer becomes ∣ ∣ ∣ ∣ 4 π − 2 π − 4 π ∣ ∣ ∣ ∣ = 2 π
define two integrals: ( I 1 , I 2 ) = ( ∫ 0 ∞ sin ( x ) S I ( x ) d x , ∫ 0 ∞ cos ( x ) C i ( x ) d x ) consider the first integral: I 1 = ∫ 0 ∞ sin ( x ) S I ( x ) d x = ∫ 0 ∞ sin ( x ) ∫ ∞ x t sin ( t ) d t d x by using integration by parts ∫ a ′ b = a b − ∫ a b ′ a ′ = sin ( x ) → a = − cos ( x ) , b = ∫ ∞ x t sin ( t ) d t → b ′ = x sin ( x ) I 1 = − cos ( x ) ∫ ∞ x t sin ( t ) d t ∣ 0 ∞ − ∫ 0 ∞ x − cos ( x ) sin ( x ) d x I 1 = 2 π + 2 1 ∫ 0 ∞ x sin ( 2 x ) d x = 4 3 π
similarly, I 2 = sin ( x ) ∫ ∞ x t cos ( t ) d t ∣ 0 ∞ − ∫ 0 ∞ x cos ( x ) sin ( x ) d x using l'hopital rule on the first part x → 0 lim sin ( x ) ∫ ∞ x t cos ( t ) d t = x → 0 lim csc ( x ) ∫ ∞ x t cos ( t ) d t = x → 0 lim − cos ( x ) / sin 2 ( x ) cos ( x ) / x = − x → 0 lim x sin 2 ( x ) = 0 I 2 = 0 − 2 π = − 2 π I 1 + I 2 = 2 1 π 1
Problem Loading...
Note Loading...
Set Loading...
If we define g ( x ) = ∫ 0 ∞ 1 + t 2 t e − x t d t x > 0 then (differentiating within the integral sign) g ′ ′ ( x ) + g ( x ) = ∫ 0 ∞ t e − x t d t = x − 2 x > 0 Looking for a solution of the form g ( x ) = e i x a ( x ) + e − i x b ( x ) , subject to the condition e i x a ′ ( x ) + e − i x b ′ ( x ) = 0 we deduce that we require i e i x a ′ ( x ) − i e − i x b ′ ( x ) = x − 2 and hence that a ′ ( x ) = 2 i x 2 e − i x b ′ ( x ) = − 2 i x 2 e i x and so a ( x ) = α − 2 i 1 ∫ x ∞ t 2 e − i t d t b ( x ) = β + 2 i 1 ∫ x ∞ t 2 e i t d t so that g ( x ) = α e i x + β e i x + ∫ x ∞ t 2 sin ( t − x ) d t for some constants α , β . Since g ( x ) → 0 as x → ∞ , we deduce that α = β = 0 , and so g ( x ) = ∫ x ∞ t 2 sin ( t − x ) d t Integrating by parts, we see that g ( x ) = [ − t sin ( t − x ) ] x ∞ + ∫ x ∞ t cos ( t − x ) d t = ∫ x ∞ t cos ( t − x ) d t = − sin x S i ( x ) − cos x C i ( x ) (I am using the notation of this question. It is more normal to write s i ( x ) here). Thus ∫ 0 ∞ ( sin x S i ( x ) + cos x C i ( x ) ) d x = − ∫ 0 ∞ g ( x ) d x = − ∫ 0 ∞ 1 + t 2 d t = − 2 1 π making the answer 1 + 1 + 2 = 4 .